Environmental Exposure to Glyphosate and Risk of Asthma in an Ecological Study (Global Journal of Medical Research, 2021)
There is strong evidence of the link between asthma and occupational exposure to pesticides and even glyphosate in agricultural workers, but it is limited on asthma and environmental or residential exposure to these chemicals. This research analyzes the prevalence of asthma in an agricultural town with high use of pesticides, mainly glyphosate. Is an ecological study conducted in Monte Ma#xED;z, Argentina, composed of a chemical and environmental analysis to determine the burden of exposure to glyphosate and pesticides in general, and a crosssectional asthma study that uses the methodological criteria of the International Study of Asthma and Allergies in Childhood (ISAAC); the prevalence#x2019;s found in Monte Ma#xED;z are compared with the results of ISAAC in Argentine cities with low exposure to pesticides. In Monte Ma#xED;z area 975 tons of pesticides are sprayed (650 are glyphosate) that are also stored inside the town.
Keywords: asthma; environmental exposure; pesticides; glyphosate; environmental health